168k views
5 votes
Use the variation of parameters method to solve the DE y"+y'- 2y=1

User Gardarh
by
5.8k points

1 Answer

6 votes

Answer:


y(t)\ =\ C_1e^(-2t)+C_2e^t\ -\ (1)/(2)

Explanation:

Given differential equation is

y"+y'-2y = 1


=>\ (D^2\ +\ D\ -\ 2)y\ =\ 1

Hence, the characteristics is


D^2+D-2\ =\ 0


=>\ D^2\ +\ 2D\ -\ D\ -2\ =\ 0


=> (D+2)(D-1) = 0

=> D = -2, 1

The general equation of the given differential equation is


y_c(t)\ =\ C_1e^(-2t)+C_2e^t

Let's consider that


y_1(t)\ =\ e^(-2t)
y_2(t)\ =\ e^(t)


y'_1(t)\ =\ -2e^(-2t)
y'_2(t)\ =\ e^t

g(t) = 1

Wronskian can be given by,

W = y_1(t)y'_2(t) - y_2(t)y'_1(t)


=\ e^(-2t).e^t\ -\ e^(t).(-2e^(-2t))


=\ e^(-t)\ +\ 2e^(-t)


=\ 3e^(-t)

Now, the particular integral can be given by


y_p(t)\ = \ -y_1(t)\int{(y_2(t).g(t))/(W)dt}\ +\ y_2(t)\int{(y_1(t).g(t))/(W)dt}


=\ -e^(-2t)\int{(e^t* 1)/(3e^(-t))dt}\ +\ e^t\int{(e^(-2t)* 1)/(3e^(-t))dt}


=\ -e^(-2t)\int{(e^(2t))/(3)dt}\ +\ e^t\int{(e^(-t))/(3)dt}


=\ (-e^(-2t))((e^(2t))/(6))\ +\ (e^t)((e^(-t))/(-3))


=\ (-1)/(6)\ -\ (1)/(3)


=\ (-3)/(6)


=\ (-1)/(2)

Now,


y(t)\ =\ y_c(t)\ +\ y_p(t)


=\ C_1e^(-2t)+C_2e^t\ -\ (1)/(2)

Hence, the complete solution of the given differential equation is


y(t)\ =\ C_1e^(-2t)+C_2e^t\ -\ (1)/(2)

User Rmorrin
by
5.0k points